2009
DOI: 10.1093/eurheartj/ehp071
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic significance of sustained ventricular tachycardias in heart failure patients implanted with biventricular pacemakers without a back-up defibrillator: results from the prospective, multicentre, Mona Lisa cohort study

Abstract: The incidence of sustained VT remains relatively low in the first year after CRT-P implantation, but when present appears closely associated with short-term adverse outcomes, especially SCD. This emphasizes the possible value of remote monitoring to detect high-risk patients for urgent upgrading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Again, our results corroborate those findings. There were only two presumed sudden cardiac deaths over a period of one year in the 198 CRT-P patients naïve to cardiac pacing included in the Mona Lisa study (9). A different study reported a 1.9% risk of sudden cardiac death per year in CRT-P patients previously naïve to cardiac pacing (24).…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, our results corroborate those findings. There were only two presumed sudden cardiac deaths over a period of one year in the 198 CRT-P patients naïve to cardiac pacing included in the Mona Lisa study (9). A different study reported a 1.9% risk of sudden cardiac death per year in CRT-P patients previously naïve to cardiac pacing (24).…”
Section: Main Findingsmentioning
confidence: 99%
“…On one hand, the majority of CRT upgrades are performed in patients with an LV ejection fraction <35%, thus fulfilling ICD implantation criteria according to the Sudden Cardiac Death in Heart Failure Trial (SCD-HeFT) (7). On the other hand, some studies suggested that de novo CRT-P patients and those upgraded from pacemaker to CRT-defibrillator (CRT-D) have a low annual risk of sustained ventricular arrhythmias and sudden cardiac death (8)(9)(10). In addition, chronically RV paced heart failure patients may respond even better to CRT with greater improvements in ejection fraction and intraventricular dyssynchrony than heart failure patients without RV pacing (11).…”
Section: Bradycardia Indications Who During Follow-up Develop Severmentioning
confidence: 99%
“…611 The following parameters may warn of impending ADHF or other cardiovascular events and predict poor clinical outcome: (i) sustained decrease in thoracic impedance due to lung fluid retention 5–8,1215 (measured between a lead in the right ventricle and the generator in the left pectoral region or using alternative current pathways); 1618 (ii) low heart rate variability, indicating sympathetic dominance in cardiac autonomic control; 6,7,12,1922 (iii) a high resting heart rate or relatively high mean heart rate over 24 h; 6,19,21,2325 (iv) decreased patient activity, potentially reflecting exercise intolerance; 7,12,1921 (v) increased frequency of ventricular extrasystoles; 26 (vi) ventricular tachyarrhythmia episodes or defibrillation shocks; 7,27,28 (vii) prolonged duration of atrial fibrillation; 7,21,22 (viii) rapid ventricular rate during atrial fibrillation; 7,21 (ix) reduced cardiac resynchronization pacing percentage, indicating a failure in the electrical treatment of cardiac asynchrony; 7,29 (x) minute ventilation disturbances; 30 and (xi) haemodynamic deterioration monitored with impedance-based or pressure sensors. 8,16,18,31,32 Combining several of these parameters into a single algorithm may improve the overall ability to risk-stratify patients with implanted devices.…”
Section: Introductionmentioning
confidence: 99%
“…The implantation technique has already been described. 14 Because of procedural difficulties, only 74 of the 86 included patients could benefit from the implantation of a left ventricular lead. The patients in whom we failed to implant a left ventricular lead (ie, in whom resynchronization therapy could not be achieved) were not followed up.…”
Section: Methodsmentioning
confidence: 99%